Meningkatkan Kreatifitas Siswa Kelas X Melalui Pembelajaran Menulis Cerpen (Hikayat) di SMA Negeri 4 Palembang - Depi Anjani; Hastari Mayrita; Mursalina Mursalina (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
This activity aims to increase the creativity of grade X students of SMA Negeri 4 Palembang through learning to write short stories (hikayat). The method uses a collaborative traditional story approach design. This action involves Indonesian language teachers as partners in the planning, implementation and evaluation process. Data was collected through observations, interviews, and analysis of the results of short story writing activities through students' writing. The results of the activity showed that learning to write short stories (hikayat) can increase students' creativity, by significantly increasing the aspects of imagination, originality, and authenticity of this learning also increases students' motivation and interest in writing. Therefore, learning to write short stories (hikayat) can be an effective strategy to increase students' creativity at SMA Negeri 4 Palembang